On the coordinated approximation method for nonlinear ill-posed problems - Pham Ky Anh (Український математичний журнал, 1994)
A generalization of the method of coordinated approximation suggested by Yu. Gaponenko [1] for the space L₂(0,1) is developed for abstract Hilbeit spaces. In particular, it is shown that, for L₂(0,1), some assumptions concerning an exact solution can be weaken. Наведено узагальнення на абстрактний простір Гільберта узгодженої апроксимації, запропонованої Ю.Л. Гапоненком для простору L₂(0,1). Зокрема показано, що для L₂(0,1) деякі умови відносно точного розв'язку можуть бути послаблені.